2015
DOI: 10.1186/s12984-015-0061-1
|View full text |Cite
|
Sign up to set email alerts
|

Neuron matters: electric activation of neuronal tissue is dependent on the interaction between the neuron and the electric field

Abstract: In laboratory research and clinical practice, externally-applied electric fields have been widely used to control neuronal activity. It is generally accepted that neuronal excitability is controlled by electric current that depolarizes or hyperpolarizes the excitable cell membrane. What determines the amount of polarization? Research on the mechanisms of electric stimulation focus on the optimal control of the field properties (frequency, amplitude, and direction of the electric currents) to improve stimulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
84
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(87 citation statements)
references
References 84 publications
3
84
0
Order By: Relevance
“…Moreover, recent researches 46,50,52,55,57 suggest that the modeling of neuronal networks as mere an ensemble of physical connections (biochemical or electrical) among neurons is incomplete unless it also includes effusive extra-neuronal phenomena such as electric and magnetic fields. Indeed, the dynamics of the neuronal activity may get affected because of the fluctuation in the inter-and extra-cellular ion concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, recent researches 46,50,52,55,57 suggest that the modeling of neuronal networks as mere an ensemble of physical connections (biochemical or electrical) among neurons is incomplete unless it also includes effusive extra-neuronal phenomena such as electric and magnetic fields. Indeed, the dynamics of the neuronal activity may get affected because of the fluctuation in the inter-and extra-cellular ion concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…This work supports our hypothesis that biological effects of electric stimulation is a function of both the field parameters and the cellular properties. [39] 4.1 Induced charges and vesicle deformation Our model predicts that the direction of vesicle deformation depends on the dielectric properties of the vesicle (see Figure 2). Prolate deformation will occur along the symmetry axis that aligns parallel to the field if the cytoplasm is more conductive than the medium (see Figure 2A), and an oblate deformation will occur if the medium is more conductive than the cytoplasm (see Figure 2B).…”
Section: Discussionmentioning
confidence: 99%
“…A detailed review on this topic could be found elsewhere. [39] 4.4 Future directions Several assumptions have to be made in the model to simplify the calculation. It did not include other mechanical considerations such as shear elasticity of the membrane [3] and ion movement through field-induced pores, which will affect electric fields [51] and vesicle shapes.…”
Section: Discussionmentioning
confidence: 99%
“…Using a back-of-the-envelope-type estimation, assuming an applied magnetic field of 1000 Oe, an MENP with an α of 100 mV cm −1 Oe −1 would generate an electric field of 100 V/cm (10 4 V/m). Generating such a field across the membrane would be sufficient to trigger firing of an action potential by a single nanoparticle (Ye and Steiger 2015). Furthermore, when acted collectively and under application of periodic signals corresponding to periodic rhythms of brain waves, MENPs could easily provide highefficacy stimulation.…”
Section: Wireless Stimulation Of Central and Peripheral Nervous Systementioning
confidence: 99%